PsycEXTRA Dataset 2011
DOI: 10.1037/e695232011-001
|View full text |Cite
|
Sign up to set email alerts
|

Parental Expectations and Academic Achievement: Mediators and School Effects

Abstract: One of the few ideas in psychology that is nearly beyond question is that parental expectations an d aspirations have substantial, or even large, effects on the achievements of their children. However, things may not be as straightforward as "expectations influence achievement." The present study used multi-level modeling to examine the effects of parental expectations at the individual level as well as at the school level on student achievement. In addition, the role of students' academic self-concept as a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
1
3
0
1
Order By: Relevance
“…Furthermore, and although this was not a main focus of the empirical work, feeling supported by parents (Chapter 5) and reporting little negative affect and emotional stability (Chapter 7) was associated with better functioning more generally. This also corroborated previous work on the role of parental expectations (e.g., Chatterjee & Sinha, 2013;Grossman et al, 2011) and negative affectivity (Kotov et al, 2010;Krueger & Markon, 2006;Lahey, 2009) in psychosocial functioning.…”
Section: Integration In Broader Literature and Implicationssupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, and although this was not a main focus of the empirical work, feeling supported by parents (Chapter 5) and reporting little negative affect and emotional stability (Chapter 7) was associated with better functioning more generally. This also corroborated previous work on the role of parental expectations (e.g., Chatterjee & Sinha, 2013;Grossman et al, 2011) and negative affectivity (Kotov et al, 2010;Krueger & Markon, 2006;Lahey, 2009) in psychosocial functioning.…”
Section: Integration In Broader Literature and Implicationssupporting
confidence: 90%
“…Similarly, feeling as though one's parents expect one to do well in secondary school may result in adolescents having less doubts themselves, which may also lead to better educational and psychological adjustment post-transition (Chatterjee & Sinha, 2013;Grossman et al, 2011). To the best of our knowledge, there is no research examining the role of both adolescent and parental pre-transition expectations in post-transition adjustment to secondary school (and many studies following adolescents after the start of secondary school, as pointed out in Jindal-Snape & Cantali, 2019).…”
Section: Parental and Own Expectations Regarding Secondary School And...mentioning
confidence: 99%
“…Expecting that one will do well academically and socially in the new school environment may result in a more positive and resilient approach to the school transition than expecting that one will not be able to keep up academically and will make no friends (e.g., Waters et al, 2014), and thus may ultimately lead to an easier transition. Similarly, feeling as though one's parents expect one to do well in secondary school may result in adolescents having less doubts themselves, which may also lead to better educational and psychological adjustment post-transition (Chatterjee & Sinha, 2013;Grossman et al, 2011). To the best of our knowledge, there is no research examining the role of both adolescent and parental pre-transition expectations in post-transition adjustment to secondary school (and many studies following adolescents after the start of secondary school, as pointed out in Jindal-Snape & Cantali, 2019).…”
Section: Parental and Own Expectations Regarding Secondary School And...mentioning
confidence: 99%
“…In addition to sleep, other variables may impact college students' academic performance, such as parental expectation and socioeconomic status (Grossman, Kuhn-McKearin, & Strein, 2011;Pearce, 2006;Vartanian, Karen, Buck, & Cadge, 2007). When assessing 5 th grade students and following up with the same population at 8 th grade, Grossman et al (2011) found that parental expectation, gender, and socioeconomic status were correlated with student achievement. In Vartanian et al's (2007) study, they found that Asian parents had high expectations for their children to complete college.…”
Section: Academic Performancementioning
confidence: 99%